Optically coupled engineered upconversion nanoparticles and graphene for a high responsivity broadband photodetector. Issue 19 (8th May 2019) - Thakur, Mukesh Kumar; Gupta, Akash; Fakhri, Muhammad Yusuf; Chen, Ruei San; Wu, Chien Ting; Lin, Kung Hsuan; Chattopadhyay, Surojit
Abstract : Upconversion nanoparticles on graphene based broadband photodetector showing unprecedented values of device parameters is demonstrated with response even for hand held domestic appliances. Abstract : A hybrid upconversion nanoparticle (UCNP)–graphene composite is demonstrated as a high-sensitivity and high-gain photodetector. The 980 nm multiphoton absorbing UCNPs are used as the photoabsorber, and optimized graphene is used as an efficient charge transporter. Although this device class is in its infancy, we show how critical engineering of the UCNPs, with a silica (SiO2 ) shell, helps to couple it optically with graphene to get a superior device. This initial report of UCNP–graphene optical coupling is expressed as fluorescence enhancement/quenching of the former in the presence of the latter. While the published literature relies mostly on fluorescence quenching in the UCNPs, our devices use both fluorescence quenching (using core UCNPs), and enhancement (using UCNP@SiO2 ) to significantly enhance the detector parameters. For example, the photoresponsivity of the core-UCNP device was ∼1.52 × 10 4 A W −1 which could be improved to ∼2.7 × 10 4 A W −1 (at 980 nm, power density of ∼31.84 μW cm −2, and under a 1.0 V bias) with the UCNP@SiO2 device. The responsivity, gain, and detectivity thus obtained are the highest reported so far for this class of composite photodetectors. The device could detect signals from domestic hand-held appliances such as laser pointers, cellphone flashlights, and air-conditioning remotes. This work will further the knowledge of device photophysics in this class of hybrids.